Parameter Matching and Optimization of Composite Clean Energy Power Supply For PHEV. Issue 3 (July 2021) - Sun, Jingxia
Abstract: The idea of composite power supply solves the problem that the specific power and specific capacity of a single battery restrict each other. The specific power of composite power supply is higher than that of a single battery, and the specific energy is higher than that of a single super capacitor, so that the power components are no longer restricted by a single factor. According to the performance requirements of the vehicle, the basic parameters of each component of the vehicle power supply are determined, and then the components are matched reasonably according to their performance advantages to get the appropriate power supply required by PHEV. The parameters of the composite power supply are optimized by using the iterative algorithm of dynamic programming to achieve the best matching of power and energy, and the matching results are verified by simulation.